Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2174/1874340400802010071
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Response Network in Animals: Proposals to Develop a Predictive Mathematical Model

Abstract: Abstract:Increasing evidence indicates that numerous genetic pathways responding to environmental stress in animals are regulated co-ordinately as well as independently. These stress-response systems should therefore be viewed in holistic terms as a network. As such, their behaviour is susceptible to mathematical modelling using a systems biology approach. This review outlines relevant evidence and describes a newly launched project to develop just such a model using stressresponse data from multiple transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Far greater detail would be obtainable using gene-arrays to investigate global or pathway-specific patterns of gene expression (transcriptome analysis), but this would be prohibitively expensive for testing many different toxicants at multiple doses and time points, let alone extending such work to mixtures. GFP-reporter responses can be used for initial screening to identify unusual or interesting patterns of response (whether to single toxicants or mixtures), which could then be further investigated using gene arrays (de Pomerai et al 2008 ). The responses described here are robust, reproducible and easily measured in a microplate format, lending themselves readily to high-throughput screening methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Far greater detail would be obtainable using gene-arrays to investigate global or pathway-specific patterns of gene expression (transcriptome analysis), but this would be prohibitively expensive for testing many different toxicants at multiple doses and time points, let alone extending such work to mixtures. GFP-reporter responses can be used for initial screening to identify unusual or interesting patterns of response (whether to single toxicants or mixtures), which could then be further investigated using gene arrays (de Pomerai et al 2008 ). The responses described here are robust, reproducible and easily measured in a microplate format, lending themselves readily to high-throughput screening methods.…”
Section: Discussionmentioning
confidence: 99%
“…Another master regulator controlling multiple stress-response pathways is the zinc-finger transcription factor SLR-2 (Kirienko and Fay 2010 ). Testing multiple output genes simultaneously allows insight into the patterns of stress response within the test organism, and this approach is greatly facilitated by the use of green fluorescent protein (GFP) reporters (Chalfie et al 1994 ; de Pomerai et al 2008 ). Although hitherto applied only to single output genes, similar tests can also be used to assess the toxicity of field samples of metal-contaminated water and soils (Mutwakil et al 1997 ; Power and de Pomerai 1999 ), and have previously demonstrated synergistic effects for metal mixtures (Power et al 1998 ; Chu and Chow 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other strains were supplied as integrated promoter::GFP fusions by the Baillie Genome GFP Project (Simon Fraser University, Burnaby, Vancouver, Canada), each containing about 3 kb of upstream promoter sequence (apart from BC20306 which contains only the 250 bp of promoter separating the cyp-34A9 gene from its upstream neighbour cyp-34A10) [2,13]. These are:-BC17553 (T09A12.2 glutathione peroxidase designated GPA::GFP), BC20303 (hsp-6::GFP), BC20305 (C11E4.1 glutathione peroxidise designated GPB::GFP), BC20306 (cyp-34A9::GFP), BC20308 (hsp-3::GFP), BC20309 (mtl-1::GFP), BC20314 (elt-2::GFP), BC20316 (gst-1::GFP), BC20329 (skn-1::GFP), BC20330 (gst-4::GFP), BC20333 (sod-4::GFP), BC20334 (cyp-29A2::GFP), BC20336 (ctl-2::GFP), BC20337 (hsf-1::GFP), BC20342 (mtl-2::GFP), BC20343 (hsp-60::GFP), BC20349 (C12C8.1 hsp-70 designated cHSP70::GFP) and BC20350 (sod-1::GFP).…”
Section: Methodsmentioning
confidence: 99%
“…Several of these pathways can be activated by a single agent: cadmium (Cd) is genotoxic, binds to reduced glutathione thus increasing ROS levels, and is a potent inducer of hsp expression. Paradoxically, cadmium can also induce the expression of multiple cytochrome P450 (cyp) genes, as revealed by gene-array studies in the nematode C. elegans [1]; we and others have demonstrated that for the cyp-34A9 gene at least, Cd regulation is probably mediated by the DAF-16 transcription factor regulating longevity [2,3]. Indeed, DAF-16 acts as a positive regulator for many other stress-response genes, including sod-3 (mitochondrial superoxide dismutase) and mtl-1 (metal-binding metallothionein) as well as hsp-16.1 and hsp-16.2 (encoding small hsp's) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The IIS pathway comprises a receptor that signals to a PI3 kinase/AKT conserved pathway which, finally, downregulates to DAF-16 activity by inhibiting its translocation into the nucleus. Thus, the major downstream target of IIS is DAF-16, the sole C. elegans ortholog of the FOXO family of transcription factors, and its translocation induces the expression of cytoprotective proteins such as heat shock proteins (HSPs), some antioxidant enzymes (superoxide dismutase and catalase), and other proteins against stress (de Pomerai et al 2008;Hsu et al 2003). HSPs are evolutionarily conserved chaperones present in all cellular compartments and classified according to their molecular weight.…”
Section: Introductionmentioning
confidence: 99%